Recommendations on bioanalytical method stability implications of co-administered and co-formulated drugs by Global CRO Council for Bioanalysis (GCC). (September 2012) - Lowes, Steve; Boterman, Mark; Doig, Mira; Breda, Massimo; Jersey, Jim; LeLacheur, Richard; Shoup, Ronald; Garofolo, Fabio; Dumont, Isabelle; Martinez, Suzanne; Needham, Shane; Zimmer, Jennifer; et al.
An open letter written by the Global CRO Council for Bioanalysis (GCC) describing the GCC survey results on stability data from co-administered and co-formulated drugs was sent to multiple regulatory authorities on 14 December 2011. This letter and further discussions at different GCC meetings led to subsequent recommendations on this topic of widespread interest within the bioanalytical community over the past 2 years.